„Bojaźń i lęk” (Rdz 9,2), czyli o zwierzętach, które wyszły z arki… Znaczenie regulacji dotyczących relacji między człowiekiem i zwierzętami w Rdz 9,1-7 - Napora, Krzysztof (Verbum Vitae, 2017)
Even a cursory reading of Gen. 9:1-7 reveals a text of great richness and complexity. By his blessing, God favors Noah and his sons with a power that assures not only the numerical growth of the human population but also its diversification according to human families, languages, lands, nations, and genealogies. God’s blessing also delineates the separation between humans and animals. For the animals, this separation is ensured by the “fear and dread” they will experience when faced with human beings. On the human side, it is marked by dominion over the animal kingdom, extending even to the possibility of killing animals for food. In this way, the violence that was a cause of the cataclysm, and threatened human beings even after the Flood, finds a proper outlet for its destructive, chaotic power. This concession–the killing of animals for food—does not permit unrestricted violence in the sphere of human-animal relations, however. Rather, it is structured and controlled by ritual law, which clearly defines its limits. What seems like a body of purely ritual law concerning the relationship between humans and animals (Gen 9:4) actually becomes a passageway to the complexity of relationships between humans. In fact, proceeding from Gen. 9:4 to Gen. 9:5-6 a shift occurs from animal to human being, from animal blood to human blood, from the value of animals to the value of human lives. The most important transition occurs between the sphere of ritual and that of ethics. Through the metaphor of ritual law, the latent nature of death is revealed, and human beings are invited to discover truths about human society. This society can only be built according to the structure provided by ethics, based on the truth that “in his own image God created humankind” (Gen. 9:6). In a deep sense, this ritual law opens out into the sphere of human society and interpersonal relationships, pointing to the realm of ethics.